THE RETURN OF THE MILITARY POLICE: ERASURES AND THE EFFECT OF MEANING IN THE DISCOURSE ON THE 2017 MILITARY POLICE STRIKE IN ESPÍRITO SANTO (PERcursos Linguísticos, 2026)
This article assembles a series of fragments from the discourse of the newspaper A Tribuna about the 2017 Espírito Santo Military Police Strike. Using the theoretical framework of materialist discourse analysis, based on the work of Michel Pêcheux, and the analytical framework DAM (Discourse, Archive, and Montage) proposed by Mara Glozman, we present the material elements of the protest and demonstration discourses that resonated in the newspaper around the "return of the Military Police." The analysis utilized the concepts of interdiscourse, discursive formation, and discursive process to describe and interpret the discursive materiality gathered. Based on the description and interpretation of this series, we identified that the phrase "The return of the Military Police" functioned by suppressing the phrase "to work," erasing the political and social relations resulting from the military police strike and producing meanings that negated or erased the strike as an event.
Keywords: Media discourse.; Strike.; Military police.; Erasure.